One patient, two diseases: collaboration in controlling TB and HIV in the Free State - Peters, Annatjie; Heunis, Christo (University of the Free State, 2005)
A perilous synergism exists between TB and HIV/AIDS, which form a dual epidemic requiring joint action. This paper first reviews key global and South African policy developments in relation to TB-HIV/AIDS control. Secondly, the early response of the Free State to global and national directives to implement integrated TB-HIV/ AIDS programmes is described. As is clear from the experience of the first TB-HIV training site in the Free State, the Mafube local municipality, integrated TB and HIV/AIDS control is made possible by means of actual practical interventions as well as the collaboration of a range of role-players. In Mafube, and later also in the Free State at large, attempts at integration have resulted in substantially more TB patients undergoing voluntary counselling and testing for HIV.

‘n Gevaarlike sinergisme bestaan tussen TB en MIV/VIGS. Hierdie siektes vorm ‘n dubbele epidemie wat tweeledige optrede vereis. Die artikel bied eerstens ’n oorsig van die internasionale en Suid-Afrikaanse beleidsontwikkelinge wat verband hou met die beheer van TB-MIV/VIGS. Tweedens word die vroeë respons van die Vry- staat op internasionale en nasionale voorskrifte om geïntegreerde TB-MIV/VIGS- programme te implementeer, beskryf. Soos blyk uit die ervaring van die eerste TB- MIV-opleidingsarea, die Mafube plaaslike munisipaliteit, word geintegreerde TB- en MIV/VIGS-beheer moontlik gemaak deur werklike praktiese intervensies, asook die samewerking van ’n reeks rolspelers. In Mafube, en later ook in die Vrystaat as ’n ge- heel, het pogings tot integrasie ’n substansiële toename in die aantal TB-pasiënte wat vrywillige berading en toetsing vir MIV ondergaan, tot gevolg gehad.
Keywords: Tuberculosis control; Tuberculosis; HIV and AIDS; Free State; South Africa